Study on the Uneven Settlement Patterns at the Bottom of Seepage Control Structures in Deep Backfilled Reservoir Basins - Meng Yayun; Wang Xianfei; Ye Xiangfei; Liu Yaolai; Yuan Li; Peng Shuairan (E3S Web of Conferences)
When a pumped storage power station adopts a full reservoir basin seepage control scheme, significant uneven settlement may occur at the bottom if there is a deep backfilled area, which could lead to cracks in the seepage control structure and threaten the system's safety. This study analyzes the basic patterns of uneven settlement in the bottom of the seepage control structure in deep backfilled basins. Using a finite element deformation gradient method, risk areas were identified, and the influence of material parameters in the backfilled area on uneven settlement was considered. The results showed that uneven settlement is particularly evident near the boundary of the excavation-backfill line and dam body boundary, with deformation gradient values exceeding the critical 1.0% mainly in corner areas of the excavation-backfill boundary, although the overall affected area is relatively small. From the perspective of material parameters, proper compaction in the backfilled areas, especially near the excavation-backfill boundary and dam body boundary, can effectively reduce uneven settlement at the reservoir bott.